2011
DOI: 10.1016/j.jcmg.2011.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of CT Angiography in Patients With Inconclusive Functional Stress Tests

Abstract: Among patients with inconclusive functional stress tests, the noninvasive assessment of CAD severity by coronary CTA has been shown to provide incremental prognostic information beyond the evaluation of traditional risk factors and coronary artery calcium score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 20 publications
0
24
0
2
Order By: Relevance
“…A timely diagnosis with coronary artery disease (CAD) is imperative in light of the morbidity and mortality of that concerns the disease (1). Invasive coronary angiography (ICA) is the gold standard for identifying coronary artery stenosis; however, it is an invasive process with very high radiation exposure (2).…”
mentioning
confidence: 99%
“…A timely diagnosis with coronary artery disease (CAD) is imperative in light of the morbidity and mortality of that concerns the disease (1). Invasive coronary angiography (ICA) is the gold standard for identifying coronary artery stenosis; however, it is an invasive process with very high radiation exposure (2).…”
mentioning
confidence: 99%
“…Regarding cardiac CT, a recent series of studies have shown that, not only the CACS assessment, but also the assessment of coronary anatomy by use of CCTA provide important prognostic information in patients suspected of having significant CAD 42,44,45,[47][48][49] . Using a 16-row detector CT device, Min et al 44 have studied 1,127 patients and assessed the relationship between all-cause mortality and the results of CCTA.…”
Section: Prognostic Valuementioning
confidence: 99%
“…In a recent study, Azevedo et al 48 have assessed 529 patients suspected of having obstructive CAD, who had undergone ischemia tests with inconclusive results. Those authors have shown that 70% of those patients had no significant obstructive lesion.…”
Section: Prognostic Valuementioning
confidence: 99%
“…The recent technical development of multi-detector computed tomography (MDCT) has rendered it feasible to calculate CACS and to detect coronary artery plaque or obstructive coronary lesions using CT coronary angiography (CT CA). The presence of obstructive coronary lesions, noncalcified coronary plaque (NCP) or the number of coronary plaques detected by CTCA improves the prediction of cardiac events over and above conventional risk scores and CACS [3][4][5][6]. Moreover, NCP with both a low CT value and positive remodeling is associated with the subsequent development of acute coronary syndrome (ACS) [7].…”
Section: Introductionmentioning
confidence: 99%